PENENTUAN EFISIENSI INHIBISI REAKSI KOROSI BAJA MENGGUNAKAN EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L) - Yuli Rizky Ananda Nasution; Sri Hermawan; Rosdanelli Hasibuan (Talenta Publisher (Universitas Sumatera Utara), 2012)
Garcinia mangostana peel extract is a natural inhibitor that can be used to inhibit the corrosion reaction rate. This research begins by extracting Garcinia Mangostana pods by maceration followed by evaporation and extracts used as the inhibitor with concentration 600, 800 and 1000 ppm, with the test sample of corrosion is steel 1 × 2 cm with the thickness is 0,1 cm and corrosive medias are sea water, rain water and sulfuric acid 1 M. The highest inhibition efficiency generated is 99,22% with ethanol solvent at concentration of 800 ppm inhibitor in rain water corrosive media; which means that Garcinia mangostana peel extract more efficiently used in rain water corrosive media.